Hazard Analysis Critical Control Points (HACCP) – Getting Started, Preliminary Steps - Ronald H. Schmidt; Debby Newslow (EDIS)
FSHN07-01, a 4-page factsheet by Ronald H. Schmidt and Debby Newslow, reviews the preliminary steps that are necessary for putting a HACCP program into place and includes tips for making sure the process happens smoothly. Published by the UF Department of Food Science and Human Nutrition, June 2007 and reviewed January 2017.